1993
DOI: 10.1021/ma00057a016
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of mixtures of polymers in aqueous solution using Fourier-transform infrared spectroscopy

Abstract: A new method is presented to determine the phase diagram of mixed aqueous biopolymer systems using Fourier transform infrared spectroscopy coupled with partial least-squares analysis. We present the equilibrium phase diagrams of aqueous amylopectin/gelatin mixtures allowed to phase separate at a temperature outside the range within which either polymer could gel. The method is capable of detecting the changes in the phase diagram when the molecular weight of one of the components is altered. The phase diagrams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 7 publications
0
28
0
1
Order By: Relevance
“…For systems where χ 1s =χ 2s , the tie lines are parallel 27 , unlike those in Figure 3, which are similar to the system of gelatin with higher molecular weight amylopectin 16 . The steeper tie line corresponding to the more concentrated ι-carrageenan/maltodextrin sample (Figure 3) suggests closer values of χ 1s and χ 2s at higher biopolymer concentration 27,31 .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…For systems where χ 1s =χ 2s , the tie lines are parallel 27 , unlike those in Figure 3, which are similar to the system of gelatin with higher molecular weight amylopectin 16 . The steeper tie line corresponding to the more concentrated ι-carrageenan/maltodextrin sample (Figure 3) suggests closer values of χ 1s and χ 2s at higher biopolymer concentration 27,31 .…”
Section: Discussionmentioning
confidence: 72%
“…In contrast to κ-carrageenan gels that are brittle and hard, ι-carrageenan can produce more flexible and soft gel textures that closely resemble gelatin gels. Depending on the concentration of polymer and type and concentration of cation, the gelation and melting temperatures of ι-carrageenan gels occur over a broader range and are generally higher (>50°C) 15 than for gelatin (~35°C) 16 . κ-Carrageenan shows ion-specific binding to the alkali salts such as potassium that can induce helix formation and gelation via interhelical bonding, whereas its interaction with, e.g., sodium is nonspecific and long-range.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that their micrographs appeared quite similar to those observed in a number of synthetic interpenetrating networks (referred to as IPNs) 110,111 , and showed phase separation into the two polymer networks with possible phase inversion at a certain mixture composition. Durrani et al 112,113 derived a phase diagram for the ternary amylopectin-gelatin-D 2 O mixture in the sol state by the use of Fourier transformed infrared microspectroscopy.…”
Section: Multicomponent Gelationmentioning
confidence: 99%
“…The formation of the maltodextrin gel is strongly concentration and time dependent. 15 Maltodextrin is believed to form a gel of densely packed crystallite particles.…”
Section: Experimental Composite Fabricationmentioning
confidence: 99%